PENGARUH LATIHAN PARALLEL BAR DIPS TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA TIM PENCAK SILAT PUTRA SMPN 6 RUMBAI - Santa Perdana; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted to determine whether there are parallel bar dips effects of exercise on muscle strength of arms and shoulders men's Martial atrs team so that samples can be flexibly provide maximum beating and appropriate. Research is a form of experiment, the population in this study is a martial arts team SMPN 6 Rumbai. Sample in this research is the son of Tim Pencak Silat SMPN 6 rumbai and amounted to 7 people. A sampling technique that is the overall total sampling son. The instruments used in this research is Ekspanding Dynamometer test, which aims to measure the muscle strength of the arms and shoulders men's pencak silat team. After that, if the statistical data, to test for normality with lilifors test a significant level 0,05 α. The hypothesis is the influence of exercise Parallel Bar Dips against the arm and shoulder muscle strength in men's pencak silat team. Based on the analysis of statistical data, there are an average Pree-test of 20.71 and the average post-test of 28.57, then the data is normal. Based on t test analysis produces Ttabel Thitung of 4.96 and 1.943, meaning Thitung> Ttabel. Thus, there is a parallel bar dips Effect of exercise on muscle strength in the arms and shoulders men's pencak silat team SMPN 6 Rumbai. Keywords: Parallel bar dips, muscle strength in shulder and Arm